Отрицательные меcтоимения и наречия как средcтва выражения различных негативных синтаксем в современном английском языке - Асонкова, Марина (Kalbotyra, 1990)
The present paper deals with the negative syntaxeme, which can be defined as an elementary syntactic unit (invariant), represented in the language by a system of its variants, which may be expressed by both negative pronouns and negative adverbs. The basic (prevalent) syntactico-semantic feature is the negative one, which manifests itself through the formal distributional characteristics such as the ability to combine with other syntaxemes as well as the range of their syntactic positions in sentence. The study of the syntactic semantics is what the pronominal and the adverbial elements, being the morphological means of expressing negative syntactic semantics, possess even in their name (nomination) - “the negative pronominal and adverbial elements”. It must be said that the negative pronouns and adverbs within the Modern English sentences manifestate the negative syntaxemes of substance as well as the negative ones of qualification. Thus we must pay attention to the fact that there must be a whole set of negative syntaxemes of substance and qualification in the English language. We have described (analysed) here nine of them.